Legal Protection for Women as Victims of Domestic Violence - Natalia Putri Dobonsolo; Hadi Tuasikal; Dwi Pratiwi Markus (Journal of Law Justice (JLJ), 2025)
This study aims to explore and understand how legal protection is provided to women victims of domestic violence (DV) and the forms of DV that affect women. The method used in this study is empirical legal analysis, which is descriptive and analytical in nature, with an interview approach involving five sources who have direct experience in cases of domestic violence. The novelty of this study lies in its focus on the factors that support and trigger domestic violence involving women, as well as an in-depth analysis of the legal protection provided to victims. The results of the study show that victims of domestic violence experience various forms of violence, including physical, sexual, psychological, economic, verbal, and spiritual abuse, which are influenced by factors such as patriarchal culture, misguided religious understanding, and personal problems within the household such as infidelity and economic difficulties. The conclusion of this study is that although legal protection for female victims of domestic violence already exists, there are still many factors that hinder its effective implementation, particularly those related to social stigma, legal ignorance, and limited access to legal and psychosocial services.